Understanding of the giant magnetic entropy change around the co-occurrence point of martensitic and magnetic transitions in Ni-Mn-In Heusler alloy. (1st May 2022) - Fang, Minxia; Tian, Fanghua; Cao, Kaiyan; Ke, Xiaoqin; Zhang, Yin; Yang, Sen; Zuo, Wenliang; Liu, Yao; Ma, Tianyu; Song, Xiaoping; Ji, Yuanchao; Ren, Xiaobing
Abstract: Magnetic refrigeration technique based on magnetocaloric effect has attracted increasing interest due to the high energy-converting efficiency and environmental friendliness. From application aspect, a large cooling capacity with a wide working temperature span, i.e., a combination of large isothermal entropy change (|ΔS|) and large adiabatic temperature (|ΔTad |) is desired, yet these two indices are hardly achieved. In this work, we report a combination of both large |ΔS| (40 J kg −1 K −1 ) and large |ΔTad | (15 K) under 5 T around room temperature in Ni-Mn-In Heusler alloys. This excellent combination is found to occurred near the co-occurrence point of martensitic and ferromagnetic transitions. Based on the systematic microstructure and Landau theory analysis, the magnetocaloric properties can be understood by the free energy barrier and the temperature range of field induced magnetic transition results when approaching the co-occurrence point. Our study may provide a promising strategy on designing novel magnetocaloric materials with both large cooling capacity and wide working temperature span through approaching the co-occurrence point of martensitic and magnetic transitions. Graphical abstract: Image, graphical abstract